(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
To integrate complicated socio-environmental concerns into conventional education, we need programs like Education for Sustainable Development and Education for Humanity and Peace. The adoption of these multidisciplinary methods in real classrooms could be more active, even though they have strong institutional backing from national and international organizations. We investigate the existence of more fundamental epistemological concerns that can explain the often sluggish development of interdisciplinary pedagogies without wishing to downplay the relevance and power of strong political will in fostering educational reform. Building on this conversation, we provide practical ideas that may foster the integration of Sustainability, humanity, peace, the environment, and the economy.